Caracterização do sistema nociceptina/orfanina FQ-receptor NOP na modulação da fibromialgia experimental - Dagnino, Ana Paula Aquistapase (2019)
Fibromyalgia is characterized by widespread pain, being accompanied by functional and affective disorders. This study evaluated the implication of nociceptin/orphanin FQ peptide receptor (NOPr) in a mouse model of fibromyalgia. The local Animal Ethics Committee approved the experimental protocols (15/00487). Fibromyalgia was induced in female CF-1 mice (20-24 g, 4 week-old) by reserpine administration (0.25 mg/kg; subcutaneous route), once a day, during 3 consecutive days. Control groups received vehicle. On the fourth day, mice were acutely treated with the selective NOP agonist nociceptin (N/OFQ), or with the selective peptide antagonist UFP-101, given by intraperitoneal (i.p., 0.3 5 nmol/kg), intracerebroventricular (i.c.v., 0.3-1 nmol/site), or intrathecal (i.t., 0.3-5 nmol/site) routes, 30 min before the experimental sessions. In a separate set of experiments, the animals were treated with the peptide UFP-101 (1 nmol/kg) or the non-peptide SB-612111 (6.6 μmol/kg) antagonists, given by intraperitoneal route, during three consecutive days, 30 min after daily reserpine injection. At the 4th day, mice also received the antagonist, dosed 30 min before evaluations. The animals were subjected to Von Frey, hot-plate, forced swimming, elevated plus-maze, rotarod and grasping tests. Pre-pro-nociceptin (ppN/OFQ) and NOPr expression was determined by RT-qPCR and immunohistochemistry. The [18F]-FDG microPET imaging was used to assess the brain activation patterns in reserpine-treated mice. The fiber size distribution of masseter and gastrocnemius muscles was evaluated by histological analysis. The mitochondria area and density in the skeletal muscle were analysed by transmission electron microscopy (TEM). In the acute protocols of treatment, the i.t. or i.p. administration of N/OFQ (1 nmol/site or 1 nmol/kg, respectively) significantly reduced the mechanical allodynia. However, i.p. treatment with N/OFQ at the dose of 5 nmol/kg had an opposite effect, leading to hypernociception. Concerning the UFP-101 effects, this peptide antagonist given i.c.v. (1 nmol/site), i.t. (3 and 5 nmol/site) or i.p. (1, 3 and 5 nmol/kg) significantly reduced the mechanical hypersensitivity in mice treated with reserpine. The acute treatment with N/OFQ or UFP-101 did not significantly alter the thermal hypersensivity, when given by i.c.v. or i.p. routes. The i.t. administration of N/OFQ (3 nmol/site) and UFP-101 (5 nmol/site) had a significant inhibitory effect on the thermal nociception. The immobility time was significantly inhibited by N/OFQ, given by i.c.v (1 nmol/site) or i.t. (3 nmol/site) routes. N/OFQ and UFP-101 did not modify any anxiety-related parameter. The chronic treatment with UFP-101 and SB-612111 reduced the mechanical allodynia (37 ± 8% and 43 ± 15.2%) and the thermal hypernociception (32.2 ± 5% and 45 ± 17.5%), besides improving the motor coordination in the rotational apparatus (7 and 2-fold increase in permanence time) and the grasping strength (15 ± 16% and 9 ± 5.5%), respectively. None of the antagonists altered the parameters of anxiety or depression. Reserpine-induced fibromyalgia was associated with an increase in ppN/OFQ mRNA expression in the lumbar spinal cord (day 3) and masseter (days 1 and 2), whereas NOPr mRNA expression was increased in the masseter muscle (day 1). Alternatively, NOPr m RNA expression was reduced in the thalamus/hypothalamus (day 3). The immunohistochemistry analysis revealed an increased expression of NOPr in the dorsal root ganglion (DRG; on day 4). UFP-101 led to a decrease in the [18F]-FDG metabolism in cingulate gyrus, superior colliculus, left midbrain, left inferior colliculus and right inferior colliculus of reserpine treated mice. Additionally, UFP-101 prevented reserpine-induced changes in fiber size distribution, according to the assessment of masseter and gastrocnemius histological sections. TEM analysis revealed that either the induction of fibromyalgia by reserpine, or the chronic treatment with UFP-101, did not alter the mitochondrial area or density. The expression of nociceptin and NOPr was altered in the mouse model of fibromyalgia induced by reserpine. Remarkably, UFP-101 improved the symptoms of pain, fatigue and adinamia, also recovering the brain activation patterns and the muscle fiber changes in this experimental paradigm. Our data shed new lights on the mechanisms underlying the fibromyalgia pathogenesis, supporting a role for NOPr in this syndrome.